"Free to Say No": Evoking freedom increased compliance in two field experiments. Issue 4 (4th July 2019) - Farley, Sally D; Kelly, Jennifer; Singh, Santokh; Thornton, Charles; Young, Taylor
ABSTRACT: The evoking freedom or "but you are free" (BYAF) technique is a social influence tactic that offers recipients the freedom to accept or decline a request. This research tested the effectiveness of the evoking freedom technique in two field experiments. Participants were asked either to complete a survey (Experiment 1) or to allow a stranger to borrow their mobile phone to make a call (Experiment 2) on an urban university campus. Half of the requests involved language that evoked freedom, and half of the requests were direct. In both experiments, results showed significantly greater compliance in the evoking freedom condition. This research extends previous work by demonstrating the effectiveness of the technique using a high-stakes request and in a culture other than that of France, where the majority of evoking freedom studies have been conducted.